IMPROVING THE ACCOUNTING OF LIABILITIES IN COMMERCIAL BANKS - Mingboyev Sherzod Khusanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines modern approaches to external auditing of liability accounting within the framework of International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA), and develops proposals for their adaptation to local practice. In addition, the paper substantiates the directions for maintaining liability accounting based on IFRS requirements, as well as its proper disclosure and improvement in financial statements.